Bijeenkomst tijdens verkiezingscampagne. V.l.n.r. : ?, ?, ?, ?, Frenkel Frank, Labij, Van Bladel, Kosterman (1977)
Bijeenkomst tijdens verkiezingscampagne. V.l.n.r. : ?, ?, ?, ?, Frenkel Frank, Labij, Van Bladel, Kosterman.